Symposium 2: Social presence in online learning communities - Kear, Karen (Proceedings of the International Conference on Networked Learning, 2010)
Tools for online communication are increasingly used in education, but they are not without problems. One significant difficulty is a lack of social presence. Social presence relates to the need for users to feel connected with each other and to perceive each other as real people. Low social presence can be a particular problem in text-based asynchronous systems such as discussion forums. These do not offer visual or auditory cues to communication, and there can be long delays between messages. This can lead to feelings of impersonality, and hence disengagement from online learning. The more recent literature on social presence suggests that it is influenced by the behaviour and interactions of participants, as well as by the characteristics of the communication medium. Learners in an online community can therefore increase social presence by communicating in ways which are perceived as ‘warm’ or ‘sociable’, and can compensate for the lack of richness of the medium. Moreover, features of communication systems can be used to encourage these types of interactions, and to ease communication. For example: use of member profiles can help participants feel that they know each other better; and use of synchronous communication can avoid frustrating delays between messages and responses. These possibilities, which are advocated in the research literature, also emerged from interviews carried out with students at the UK Open University. These interviews aimed to explore students’ experiences of using online communication in a distance learning course, and their ideas for improvements to online communication systems for learning. The interviews revealed problems, such as poor communication and misunderstandings, associated with a lack of social presence. Students highlighted system features that they found useful, or would like to have available, which would help to address these issues. In particular, they suggested that increased use of member profiles would help them get to know each other better, and that synchronous communication tools such as instant messaging would be of practical and social value. It is concluded that social presence in online learning communities can be enhanced by changes to the design and use of communication systems, together with attention to styles of communication within these environments.